Pregnancy Associated with Systemic Lupus Erythematosus: Immune Tolerance in Pregnancy and Its Deficiency in Systemic Lupus Erythematosus—An Immunological Dilemma - Cristina Gluhovschi; Gheorghe Gluhovschi; Ligia Petrica; Silvia Velciov; Adrian Gluhovschi (Journal of Immunology Research)
Pregnancy is a physiological condition that requires immune tolerance to the product of conception. Systemic lupus erythematosus (SLE) is a disease with well-represented immune mechanisms that disturb immune tolerance. The association of pregnancy with systemic lupus erythematosus creates a particular immune environment in which the immune tolerance specific of pregnancy is required to coexist with alterations of the immune system caused by SLE. The main role is played by T regulatory (Treg) cells, which attempt to regulate and adapt the immune system of the mother to the new conditions of pregnancy. Other components of the immune system also participate to maintain maternal-fetal immune tolerance. If the immune system of pregnant women with SLE is not able to maintain maternal immune tolerance to the fetus, pregnancy complications (miscarriage, fetal hypotrophy, and preterm birth) or maternal complications (preeclampsia or activation of SLE, especially in conditions of lupus nephritis) may occur. In certain situations this can be responsible for neonatal lupus. At the same time, it must be noted that during pregnancy, the immune system is able to achieve immune tolerance while maintaining the anti-infectious immune capacity of the mother. Immunological monitoring of pregnancy during SLE, as well as of the mother’s disease, is required. It is important to understand immune tolerance to grafts in transplant pathology.